Fibrodysplasia ossificans progressiva in a newborn with cardiac involvement. Issue 4 (25th March 2015) - Marseglia, Lucia; D'Angelo, Gabriella; Manti, Sara; Manganaro, Alessandro; Calabrò, Maria Pia; Salpietro, Carmelo; Gitto, Eloisa
Abstract Fibrodysplasia ossificans progressiva is a rare genetic disease that manifests in early life with malformed big toes and progressive heterotopic ossification that forms qualitatively normal bone in characteristic extraskeletal sites. Mutation c.617G>A in the activin A receptor type I gene is reported in all patients with fibrodysplasia ossificans progressiva. No cases of cardiac involvement have been described in children. We report the case of a child with halluces valgi at birth, along with two tender, firm, immovable masses located on the right and left parietal–occipital region, a transitory subluxation of the right hip and an unusual ventricular septal hypertrophy. We hypothesize that the ventricular septal hypertrophy could be the result of a thickening of the fibrous portion of the septum, and a possible new element of the phenotype, probably resulting from the mechanical stimuli secondary to the significant hemodynamic changes occurring at birth.